Agriculture pump sprayer trolley / Muhammad Shazril Nazmi Mohd Nizam and Abdul Hadi Abdul Rahim @ Ibrahim - Mohd Nizam, Muhammad Shazril Nazmi; Abdul Rahim @ Ibrahim, Abdul Hadi (School of Mechanical Engineering, 2023)
The agriculture sector is very important in our country. Effective methods will ease the process to produce a high-quality product. The agriculture pump sprayer trolley is used for watering and fertilizing crops. The objectives of this project are to design and analyze an Agriculture Pump Sprayer Trolley and to fabricate an affordable and functional Agriculture Pump Sprayer Trolley. The problem that users faced is most of the agriculture pump sprayer nowadays is heavy, hard to operate, and not user-friendly. Plus, most of that pump sprayer also takes time and energy to be operated because people need to bring it to their back. So, this project tries to make an affordable machine that is easy to use. The expected result is to make a functional pump sprayer for the gardener or others. In conclusion, it is hoped that this project will solve the problems that users faced